Experimental investigation of woven fabric cfrp bolted joints: parametric study - Ahmad, Hilton (ARPN Journal, 2016)
Present paper comprises a wide ranging experimental study of mechanically fastened woven CFRP using double-lap joint (DLJ) configurations. Details of the bolted joint materials and its configurations are given. This is followed by an account of the sample preparation process and a description of the range of joint types and variables investigated. Mechanical testing set-up and test method are then described. Experimental results relating to damage observations and ultimate strength are then presented. This is followed by discussion on the relationships between the bearing stress at failure and the hole size of specimens, the level of clamp-up and different joint type.